Mutilação Genital Feminina - a Importância de Reconhecer e de Saber como Agir - Campos, AC (2013)
Female genital mutilation, also named female genital cutting or female circumcision, refers to all practices involving total or partial removal of female external genitalia, or causing other lesions without an established health benefit. The World Health Organization estimates that 130 million women have been submitted to genital mutilation and 3 million are annually exposed to such risk in Africa. It has classified the practice of female genital mutation in four types. Portugal is considered a risk country for the practice of genital mutilation because of the high migration rates from the African continent, and women from Guinea-Bissau are at particular risk. A multidisciplinary commission published an Action Program in 2009, with measures directed at providing healthcare professionals with information on how to deal with this problem.